Ilmu Pengetahuan Sosial di Era Post-Truth: Prespektif Guru Sekolah Dasar - Vicky Dwi Wicaksono (Graduate School of Universitas Negeri Malang, 2021)
Abstract: The post-truth era will provide a new atmosphere in developing science. The act of lying will become a problem when it is repeated and then considered to be the truth by the wider community. The influence of the post-truth era is also in the subject of Social Sciences. The teacher as a teacher in the classroom has both pedagogical and professional competences. Teachers can become victims in the post-truth era, when they don't improve their competence. The purpose of this study was to determine the perspective of elementary school teachers in the subject of Social Sciences in the post-truth era. This type of research uses descriptive research with a quantitative approach. The results of the questionnaire given that teachers can be influenced by alternative facts are 76.8%, while scientific facts get 68.4%. Alternative facts are dominant in social studies learning in SD. This condition will be detrimental to students in obtaining real knowledge.Abstrak: Era post-truth akan memberikan suasana yang baru dalam mengembangkan keilmuan. Tindakan kebohongan akan menjadi permasalahan ketika dilakukan berulang-ulang dan kemudian dianggap menjadi kebenaran oleh masyarakat luas. Pengaruh era post-truth juga dalam mata pelajaran Ilmu Pengetahuan Sosial. Guru sebagai seorang pengajar dalam kelas memiliki kompetensi pedagogi dan profesional. Guru dapat menjadi korban pada era post-truth, ketika tidak meningkatkan kompetensinya. Tujuan penelitian ini mengetahui prespektif guru sekolah dasar dalam mata pelajaran ilmu pengetahuan sosial di era post-truth. Jenis penelitian ini menggunakan penelitian deskriptif dengan pendekatan kuantitatif. Hasil yang angket yang diberikan bahwa guru dipengaruhi oleh fakta alternatif sebesar 76,8%, sedangkan fakta ilmiah mendapatkan 68,4%. Fakta alternatif menjadi dominan dalam pembelajaran IPS di SD. Kondisi ini akan merugikan siswa dalam memperoleh pengetahuan yang sebenarnya.